2015
DOI: 10.1590/0004-282x20140225
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for executive functions in attention deficit and hyperactivity disorder

Abstract: This study aimed to investigate if an executive functions (EF) intervention could promote these skills in individuals with attention deficit and hyperactivity disorder (ADHD). Eighteen children and adolescents, 7-13 years old, divided into experimental (EG, N = 8) and control (CG, N = 10) groups, were assessed in the Block Design and Vocabulary subtests of the WISC III and seven tests of EF. Parents answered two scales, measuring EF and inattention and hyperactivity signs. EG children participated in a program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
11
0
7
Order By: Relevance
“…People with lower ages and higher education levels showed better performance in attentional tasks, which suggests the influence of these variables on the attention process. These data confirm what was obtained, but we cannot infer that education level influences the attentional tests (16) . The fact that stress is predominant in the resistance phase suggests that the cognitive processes investigated have undergone little variation in the proposed times.…”
Section: About Cognitive Testingsupporting
confidence: 82%
See 2 more Smart Citations
“…People with lower ages and higher education levels showed better performance in attentional tasks, which suggests the influence of these variables on the attention process. These data confirm what was obtained, but we cannot infer that education level influences the attentional tests (16) . The fact that stress is predominant in the resistance phase suggests that the cognitive processes investigated have undergone little variation in the proposed times.…”
Section: About Cognitive Testingsupporting
confidence: 82%
“…Although the methodology and population of this study is different from the one used, the neuropsychological test applied to the adults in the control group showed that the attention, memory, visualmotor dexterity and cognitive flexibility tests were not altered in those with complaints of attention deficit (5,16) . People with lower ages and higher education levels showed better performance in attentional tasks, which suggests the influence of these variables on the attention process.…”
Section: About Cognitive Testingmentioning
confidence: 86%
See 1 more Smart Citation
“…As mentioned, EF deficits in youth with ADHD correlate with impairments in self‐regulation (Barkley, ). In the present review, only two studies used neurological assessments to measure EF and monitor changes in EF following SRL interventions (i.e., Menezes, Dias, Trevisan, Carreiro, & Seabra, ; Miranda, Presentación, Siegenthaler, & Jara, ). Future studies should examine the degree of EF impairments in students with ADHD, as well as changes in EF impairment following SRL intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of time participants spent in training ranged between 375 and 3,840 min (average of 1,096 min per intervention). Two types of intervention materials were considered: computerized (Beck et al, 2010;Steiner et al, 2011Steiner et al, , 2014Green et al, 2012;Johnstone et al, 2012;Egeland et al, 2013;van der Oord et al, 2014;van Dongen-Boomsma et al, 2014;Dovis et al, 2015;Azami et al, 2016;Bigorra et al, 2016;Davis et al, 2018;Minder et al, 2018) and non-computerized cognitive training (Tamm et al, 2013;Menezes et al, 2015;Re et al, 2015;Tamm and Nakonezny, 2015;Hannesdottir et al, 2017;Qian et al, 2017;Shuai et al, 2017;Capodieci et al, 2018). One study used both types of intervention in order to compare their efficacy (van der Donk et al, 2015).…”
Section: Type Of Interventionmentioning
confidence: 99%